Zinc monotherapy is not as effective as chelating agents in treatment of wilson disease - Weiss, Karl Heinz; Gotthardt, Daniel; Klemm, Daniela; Merle, Uta; Ferenci-Foerster, Daniela; Schäfer, Mark; Ferenci, Peter; Stremmel, Wolfgang (Gastroenterology, 2011)
Background & Aims - Wilson disease is a genetic disorder that affects copper storage, leading to liver failure and neurologic deterioration. Patients are treated with copper chelators and zinc salts, but it is not clear what approach is optimal because there have been few studies of large cohorts. We assessed long-term outcomes of different treatments. - Methods - Patients in tertiary care centers were retrospectively analyzed (n = 288; median follow-up time, 17.1 years) for adherence to therapy, survival, treatment failure, and adverse events from different treatment regimens (chelators, zinc, or a combination). Hepatic treatment failure was defined as an increase in activity of liver enzymes (aspartate aminotransferase, alanine aminotransferase, and γ-glutamyltransferase) >2-fold the upper limit of normal or >100% of baseline with an increase in urinary copper excretion. - Results - The median age at onset of Wilson disease was 17.5 years. Hepatic and neuropsychiatric symptoms occurred in 196 (68.1%) and 99 (34.4%) patients, respectively. Hepatic treatment failure occurred more often from zinc therapy (14/88 treatments) than from chelator therapy (4/313 treatments; P < .001). Actuarial survival, without transplantation, showed an advantage for chelating agents (P < .001 vs zinc). Changes in treatment resulted mostly from adverse events, but the frequency did not differ between groups. Patients who did not respond to zinc therapy showed hepatic improvement after reintroduction of a chelating agent. - Conclusions - Treatments with chelating agents or zinc salt are effective in most patients with Wilson disease; chelating agents are better at preventing hepatic deterioration. It is important to identify patients who do not respond to zinc therapy and have increased activities of liver enzymes, indicating that a chelating agent should be added to the therapeutic regimen.
Online verfügbar 24 December 2010
Gesehen am 18.11.2022